A Review of Wind Turbine Noise Perception, Annoyance and Low Frequency Emission. Issue 1 (February 2013) - Doolan, Con
Current literature concerning the perception, annoyance and emission of low-frequency noise from wind turbines are reviewed. Wind turbine noise has been shown to be annoying to people with annoyance related to noise load. Other factors, such as those related to visual, economic and psychological effects, were also shown to affect a person's annoyance of wind turbine noise. Published infrasound (noise at frequencies less than 20 Hz) measurements show that levels at typical residential set-back distances are too low to be directly audible, but may be perceived via window rattling. On the other hand, low-frequency noise levels, in the frequency range of 20–200 Hz may exceed audibility thresholds and it is postulated they may be correlated with annoyance. A review of general low-frequency noise annoyance studies is presented and highlights the similarities of many wind turbine noise complaints with those due to low-frequency noise. The paper concludes with a suggestion to develop a new methodology that can simultaneously acquire annoyance and noise data at the time a person believes they are annoyed by wind turbine noise.